THE ROLE OF HRM IN TEACHER INNOVATION IN SOUTH KALIMANTAN VOCATIONAL SCHOOLS: INDUSTRY 4.0 AND SOCIETY 5.0 - Rahmi, Yulia; Bahrani, Bahrani; Narlianto, Muhammad Deddy; Khuzaini, Khuzaini; Shaddiq, Syahrial (Cendikia: Jurnal Pendidikan dan Pengajaran, 2026)
Human resources management (HRM) is crucial in educational institutions, particularly in vocational schools in South Kalimantan, where the quality of education is closely linked to the innovation and creativity of teachers. This study investigates HRM strategies and practices that enhance teacher innovation and creativity, particularly in the context of Industry 4.0 and Society 5.0. Utilizing a descriptive qualitative methodology, the research interprets dynamics within the school environment through observations, interviews, and document analysis. The findings indicate that effective HRM practices significantly contribute to cultivating an innovative culture among teachers. Key elements identified include professional development programs, collaborative teaching environments, and performance management systems that encourage creativity. The results underscore the importance of HRM in creating a conducive atmosphere for educational innovation and enhancing the overall teaching and learning process.